Study of e-DNA Quality at Fishing Ground of Manado Bay, North Sulawesi Province. - Zebua, Nistiarni; Mandagi, Ixchel F.; Masengi, K.W.A; Luasunaung, Alfret; Rumengan, Inneke F. M.; Wulur, Stenly; Makapedua, Daisy M.; Masengi, E. I. K.G.; Sumilat, Deiske A.; Masengi, Akira W. R.; Manoppo, Victoria (Jurnal Ilmiah Platax, 2025)
We used the Nansen Bottle Sampler to collect water samples in the deepsea area, ranging from 150 meters to 175 meters in six water points around Manado Bay, to test the quality of e-DNA water samples to detect target species in the fishing area. Therefore, the basis of the case study method with a sampling technique was carried out on July 29 2023 using Power Water Sterivex Kits, water samples were then stored at -250C and were then taken to TBRC, University of the Ryukyus for further laboratory works, such as; eDNA extract, eDNA quality testing, 1st and 2nd PCR and Electrophoresis eDNA analysis processes using MiFish-U primers with a target of 163–185bp and 375 bp, following the MiFish protocol.  Based on the results of the eDNA extract solution, it is known that the quality of eDNA from the 6 sampling sites locations ranged between 2.8 µg/mL – 4.4 µ g/mL, which means a good quality of eDNA. Moreover, it showed that the presence of DNA fragments at Kappa 60◦C Gelelectrophoresis 1st-PCR, 12S rRNA gene product (163–185bp), and Kappa 60◦C and 65◦C Geklelectrophoresis 2nd-PCR Products according to the target amplicon 375 bp. This means we can conduct the next step, the PCR sequence analysis.  Then, eDNA quality testing, 1st and 2nd PCR, and Electrophoresis of e-DNA analysis process were using MiFish-U F/R primers with a target of 375 bp, it is known that the concentration of Nanodrop from the 6 sampling locations ranges between 2.8 µg/mL – 4.4 µg/mL while the core or quality eDNA ranged from 1.56 µg/mL – 2.50 µg/mL. Based on identification results, five types of species were detected; Myctophum lychnobium, Selar crumenophthalmus, Photonectes sp., Oreochromis sp. Thunnus obesus and Homo sapiens were generated using eDNA metabarcoding on the mitochondria genome database MitoFish. Keywords: e-DNA, eDNA quality, species target, fishing area, Manado Bay   Abstrak Kami menggunakan Nansen Bottle Sampler untuk mengambil sampel air pada laut dalam berkisar 150meter sampai 175 meter di enam titik perairan Sekitar Teluk Manado, untuk menguji Kualitas e-DNA sample air yang digunakan untuk mendeteksi target spesies pada daerah penangkapan. Selanjutnya dasar metode studi kasus dengan teknik pengambilan sampel secara sampling dilakukan pada tanggal 29 Juli 2023 menggunakan Power Water Sterivex Kits, sapel air disimpan pada -250C yang selanjutnya dibawa ke TBRC, University of the Ryukyus untuk pnelitian laboratorium lanjutan seperti ekstrak eDNA, Pengujian kualitas eDNA, 1st and 2nd PCR dan Elektrophoresis proses analisis eDNA menggunakan primer MiFish-U dengan target 375 bp, mengikuti MiFish protokol. Berdasarkan hasil pengujian larutan ekstrak eDNA diketahui bahwa kualitas eDNA dari 6 titik lokasi sampling berkisar antara 2.8 ng/mL – 4.4 ng/mL dan menunjukkan adanya fragment DNA pada Kappa 60◦C Geklelectrophoresis 1st-PCR Produk 12S rRNA gene (163–185bp, dan Kappa 60◦C dan 65◦C Geklelectrophoresis 2nd-PCR Produk sesuai amplikon target 375 bp. Hal ini berarti dapat dilanjutkan pada tahap analisis sekuens PCR. Pengujian kualitas eDNA, 1st and 2nd PCR dan Elektrophoresis proses analisis eDNA menggunakan primer MiFish-U F/R dengan target 375 bp, diketahui bahwa konsentrasi Nanodrop dari 6 titik lokasi sampling berkisar antara 2.8 µg/mL – 4.4 µg/mL sedangkan kemurnian atau kualitas eDNA berkisar antara 1.56 µg/mL – 2.50 µg/mL. Hasil identifikasi menyatakan lima jenis spesies terdeteksi; Myctophum lychnobium, Selar crumenophthalmus, Photonectes sp., Oreochromis sp. Thunnus obesus, Homo sapiens dihasilkan dengan menggunakan eDNA metabarcoding pada MitoFish database genom mitokondria. Kata kunci : e- DNA, kualitas eDNA, target spesies, daerah penangkapan, Teluk Manado.